Existence and release of sodium in Zhundong coal: effects of treating temperature and silica additives. (2016) - Yang, Tao; Wang, Xuebin; Tan, Houzhang; Wei, Bo; Deng, Shuanghui; Zhang, Limeng; Zhang, Huiyan
Zhundong coalfield is the largest integrated coal basin in China and has been only recently discovered. Zhundong coal contains a high amount of sodium, which induces severe slagging. In this study, the existence and transformation of alkali and alkali earth metals in Zhundong coal were investigated, and the effects of treating temperature and silica additives were determined. The results show that most of the Na and partial Ca species in raw Zhundong coal and ash were soluble. Sulphates were found in ash and did not decompose until 1, 150°C. In the ash prepared at 500°C, a specific amount of MgCa(CO3 )2 was found in the ash and decomposed at >600°C. The release of Na during ashing is mainly attributed to water-soluble Na because of the insignificant change in the acid-soluble and insoluble Na content in ash with increasing treating temperature. Silica additives have an effective function in capturing Na species at high temperatures. With increasing additive mass, the relative content of water-soluble Na is significantly reduced, but more water-insoluble Na is retained in the residual ash. [Received: May 10, 2014; Accepted: August 21, 2014]